PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA RAMBUSARATU MENUJU DESA WISATA DI KECAMATAN MAMASA KABUPATEN MAMASA - Masyhadiah Masyhadiah; Yan Yan (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study aims to determine the extent of community participation in the process of developing Rambusaratu Village towards Tourism Village. The research is descriptive which analyzes the process of disseminating information about the declaration of Rambusaratu Village as a Tourism Village. The collected data was analyzed descriptively qualitatively with an interactive analysis model. The results of the analysis provided information that the process of disseminating information about the launching of Rambusaratu Village as a tourism village was carried out by all elements of the community but was not optimal and did not meet the target. Community participation can be assessed quite high because they have made real efforts even though the results were not as expected.